Think-Pair-Share and Mathematical Literacy: A Quasi-Experimental Study in Senior High School Mathematics - Andrea Putri Sabbina; Ayu Faradillah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Improving students’ mathematical literacy (ML) remains an important concern in mathematics education, particularly because Indonesian students continue to demonstrate relatively low ML performance. This study examined the effect of the Think–Pair–Share (TPS) learning model on students’ ML using a quasi-experimental posttest-only control group design. The participants were 94 Grade 10 students divided equally into experimental and control groups. Data were collected using a mathematical literacy essay test and analyzed through descriptive statistics, the Mann–Whitney U test, and Cohen’s d effect size using SPSS version 27. The Mann–Whitney U test was employed because the posttest scores did not fully satisfy the assumption of normality. The results showed no statistically significant difference in overall ML between the experimental and control groups (p = .312). Nevertheless, the effect-size analysis revealed a large positive effect on the understanding indicator (d = 1.256) and a small positive effect on communication (d = 0.190). In contrast, small and moderate negative effects were found for analysis (d = −0.233) and representation (d = −0.520), respectively, indicating slightly better performance in the control group. The overall effect size was small (d = 0.146). These findings indicate that TPS did not significantly improve students’ overall ML but may be more effective in supporting conceptual understanding than other dimensions of mathematical literacy.